2009
DOI: 10.1116/1.3151968
|View full text |Cite
|
Sign up to set email alerts
|

Versatile synthesis and micropatterning of nonfouling polymer brushes on the wafer scale

Abstract: In this article, the authors describe new approaches to synthesize and pattern surfaces with poly[oligo(ethylene glycol) methyl methacrylate] (POEGMA) polymer brushes synthesized by surface-initiated atom transfer radical polymerization. These patterned coatings confer "nonfouling" properties protein and cell resistance-to the surface in a biological milieu. The versatile routes for the synthesis of POEGMA demonstrated here offer clear advantages over other techniques previously used in terms of their simplici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 38 publications
1
62
0
Order By: Relevance
“…27 Further wetlab work with this system by Chilkoti and Zauscher in collaboration with Ratner has shown that SI-ATRP can be used to pattern non-fouling regions on surfaces that are resistant to protein and cellular adherence and absorption. 28 …”
Section: 0 Non-fouling Surface Coatingsmentioning
confidence: 99%
“…27 Further wetlab work with this system by Chilkoti and Zauscher in collaboration with Ratner has shown that SI-ATRP can be used to pattern non-fouling regions on surfaces that are resistant to protein and cellular adherence and absorption. 28 …”
Section: 0 Non-fouling Surface Coatingsmentioning
confidence: 99%
“…Polymer brushes can be described as an assembly of flexible linear macromolecules which are tethered by one end to a surface, forming a compact layer of polymer chains which are stretched perpendicularly to the surface. 43 Polymer brushes have recently attracted considerable attention, due to numerous applications in a broad range of fields, 44 such as enhancement of lubrication properties of surfaces, 45,46 tailoring of adhesion and wetting properties, 47 improvement of drugs biocompatibility, 48 creation of protective coatings to prevent protein adsorption in biological environments, 49 biomolecules analysis in microfluidic devices, 50 and design of thermosensitive surfaces or interfaces. 51 Polymer brushes have been used in combination with soft-lithography techniques to create complex three-dimensional pattern to allow the capture and release of medicine and nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…The compromise between both is offered by surface-initiated controlled radical polymerizations (SI-CRP) and especially surface-initiated atom transfer radical polymerization (SI-ATRP). 12,13 Lately, several strategies have been developed to minimize the metal (i.e. 10,11 Hence, only few reports on the large-scale synthesis of polymer brushes by SI-ATRP can be found.…”
Section: Introductionmentioning
confidence: 99%